2022
DOI: 10.1111/acer.14894
|View full text |Cite
|
Sign up to set email alerts
|

Attention bias and alcohol craving: Differential effects via biological sex and mood

Abstract: Background Attentional bias (AB) has been linked to alcohol use, mood, and alcohol craving, with key differences across different types of mood and biological sex. However, further exploration of the role of AB across these alcohol variables is needed. The current study examined the relationship between mood and AB as predictors of alcohol craving using ecological momentary assessment (EMA). Exploratory analysis examined these effects as a function of biological sex. Methods Participants (n = 69) from a Midwes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…RSA should continue their successful commitment to diversity in research participant populations and continue to advocate for diverse researchers. et al, 2020); attentional bias and mood predict alcohol craving differently between biological sexes (e.g., Moskal et al, 2022) Gender identity Percentage or number of reported gender identities; data collection should have separate items for gender identity and biological sex and allow self-identification. Badgett et al (2014) outline a recommended two-step approach using the following categories for the gender identity item: male, female, trans male/trans man, trans female/trans woman, genderqueer/gender non-conforming, different identities (please state).…”
Section: Con Clus Ionmentioning
confidence: 99%
“…RSA should continue their successful commitment to diversity in research participant populations and continue to advocate for diverse researchers. et al, 2020); attentional bias and mood predict alcohol craving differently between biological sexes (e.g., Moskal et al, 2022) Gender identity Percentage or number of reported gender identities; data collection should have separate items for gender identity and biological sex and allow self-identification. Badgett et al (2014) outline a recommended two-step approach using the following categories for the gender identity item: male, female, trans male/trans man, trans female/trans woman, genderqueer/gender non-conforming, different identities (please state).…”
Section: Con Clus Ionmentioning
confidence: 99%
“…While no association was found between negative mood and AB, positive mood predicted increases in AB and alcohol use over the same day at within-person level. Moskal et al (2022) used a similar design with EMA for 15 days to investigate the role of alcohol AB (assessed by a visual probe task) as a craving predictor. They showed that AB-craving associations were stronger as momentary positive mood and trait-like sad mood increased among men and, on the contrary, decreased among women.…”
Section: Introductionmentioning
confidence: 99%